Using a Virtual Computing Laboratory to Foster Collaborative Learning for Information Security and Information Technology Education - Abdullah Konak; Michael R. Bartolacci (Journal of Cybersecurity Education, Research & Practice)
Virtual computer laboratories have been an excellent technological solution to the problem of providing students with hands-on experimentation in information technology fields such as information security in a cost effective and secure manner. A virtual computer laboratory was utilized in this work as a collaborative environment for student learning with the goal of measuring its effect on student learning and attitudes toward laboratory assignments. Experiments were carried out utilizing specially-designed computer-based laboratory activities that included student assessments and surveys upon their completion. The experiments involved both small groups and individual students completing their respective laboratory activities and subsequent assessments/surveys. The analysis of the data collected from both versions of the activity showed that students who performed the collaborative version of the activity benefited more than students who completed it on their own with respect to their learning and attitudes towards the subject areas covered in the laboratory activities.